Klebsiella pneumoniae resistant to third‐generation cephalosporins in five African and two Vietnamese major towns: multiclonal population structure with two major international clonal groups, CG15 and CG258. (5th March 2012) - Breurec, S.; Guessennd, N.; Timinouni, M.; Le, T. A. H.; Cao, V.; Ngandjio, A.; Randrianirina, F.; Thiberge, J. M.; Kinana, A.; Dufougeray, A.; Perrier‐Gros‐Claude, J. D.; Boisier, P.; et al.
Abstract The molecular epidemiology of third‐generation cephalosporin‐resistant (3GC‐R) Klebsiella pneumoniae in developing countries is poorly documented. From February 2007 to March 2008, we collected 135 3GC‐R K. pneumoniae isolates from seven major towns in Maghreb (Morocco), West Africa (Senegal, Côte d'Ivoire), Central Africa (Cameroon), East Africa (Madagascar) and Southeast Asia (Vietnam). Their genetic diversity, assessed by multilocus sequence typing, was high (60 sequence types), reflecting multiclonality. However, two major clonal groups, CG15 (n = 23, 17% of isolates) and CG258 (n = 18, 13%), were detected in almost all participating centres. The two major clonal groups have previously been described in other parts of the world, indicating their global spread. The high diversity of enterobacterial repetitive intergenic consensus sequence‐PCR banding patterns at the local level indicates that most isolates were epidemiologically unrelated. The isolates were characterized by the presence of multiple resistance determinants, most notably the concomitant presence of the aac(6′)‐Ib‐cr, qnr and blaCTX‐M‐15 genes in 61 isolates (45%) belonging to 31 sequence types. These isolates were detected across a large geographical area including Cameroon (n = 1), Vietnam (n = 4), Madagascar (n = 10), Côte d'Ivoire (n = 12), Morocco (n = 13) and Senegal (n = 21). These results have major implications for patient management and highlight a potential reservoir for resistance determinants.